gp63 Homologues in Trypanosoma cruzi: Surface Antigens with Metalloprotease Activity and a Possible Role in Host Cell Infection - Cuevas, Ileana C. (American Society for Microbiology, 2003)
gp63 is a highly abundant glycosylphosphatidylinositol (GPI)-anchored membrane protein expressed predominantly in the promastigote but also in the amastigote stage of Leishmania species. In Leishmania spp., gp63 has been implicated in a number of steps in establishment of infection. Here we demonstrate that Trypanosoma cruzi, the etiological agent of Chagas' disease, has a family of gp63 genes composed of multiple groups. Two of these groups, Tcgp63-I and -II, are present as high-copy-number genes. The genomic organization and mRNA expression pattern were specific for each group. Tcgp63-I was widely expressed, while the Tcgp63-II group was scarcely detected in Northern blots, even though it is well represented in the T. cruzi genome. Western blots using sera directed against a synthetic peptide indicated that the Tcgp63-I group produced proteins of ∼78 kDa, differentially expressed during the life cycle. Immunofluorescence staining and phosphatidylinositol-specific phospholipase C digestion confirmed that Tcgp63-I group members are surface proteins bound to the membrane by a GPI anchor. We also demonstrate the presence of metalloprotease activity which is attributable, at least in part, to Tcgp63-I group. Since antibodies against Tcgp63-I partially blocked infection of Vero cells by trypomastigotes, a possible role for this group in infection is suggested.